Managing Information Transparency in Pondok Buntet Islamic Boarding School, Cirebon - Ade Like Rachmawati; Mochamad Asep Kuswara; Muhammad Shubhan Hudzaifa; Masdar Hilmi (Jurnal Abdimas Cendekiawan Indonesia, 2025)
Islamic boarding schools (Islamic boarding schools) currently encounter significant challenges in remaining relevant amid the swift evolution of information technology, while at the same time upholding religious and moral values. One pressing issue is the need for increased transparency in managing information, especially as digital transformation becomes inevitable. This study examines the efforts of Pondok Buntet Islamic Boarding School Cirebon in embracing digital tools to enhance governance transparency. The primary objective is to analyze how Islamic boarding schools manage information openness in the context of modernization and to explore strategies adopted by Pondok Buntet Pesantren in navigating these changes. Employing a qualitative case study approach, data were gathered through in-depth interviews with pesantren administrators and direct field observations. Findings indicate that the pesantren has initiated steps toward an information openness framework, primarily focusing on transparency in religion and community-related activities. Nonetheless, limitations such as inadequate access to technology and the absence of standardized regulations continue to hinder broader implementation. The study concludes by recommending the development of more comprehensive and accessible information systems within Islamic boarding schools to strengthen institutional accountability and transparency in the digital era.